Estimation of total Phenol and flavonoid contents of Citrus limon L Burmf leaves from North Eastern region of India. - Upadhyaya, S.; Khatiwora, E.; Bora, D.K. (Journal of Drug Delivery and Therapeutics, 2019)
Citrus plants belonging to the family Rutaceae, are traditionally used by the local people India to treat scurvy, rheumatism, stomachic, diarrhea, liver disorders and used as an antioxidant. They are valuable source of phenolic and other biologically active compounds.  Phenolic compounds have been reported to have multiple biological effects. In this paper quantitative determination of phenols and flavonoids of Citrus limon L Burmf leaves extracts was carried out using spectrophotometric methods. The plant material was collected from Assam, north eastern region of India. Total phenolic content was determined by Folin-Ciocalteu method and aluminium chloride method was used for flavonoid determination. Acetone and methanol extracts of leaves showed quite high amount of phenol as well as flavinoid contents compared to ethanol and ethyl acetate extracts.  However, all the extracts exhibited significant results.Keywords: Citrus limon, Phenol, Flavonoid, Catechol and Quercetin.